Revisiting the underground economy in Guyana 2001-2008 - Thomas, Clive Y. ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Revisits the phenomenon of the underground economy in Guyana utilising the techniques of earlier studies. Highlights some key macro-economic features of 2001-08 in order to contrast these with the circumstances prevailing in the earlier period covered by the previous studies. Presents the results from applying the methods of measurement used in earlier studies to the period of our inquiry (2001-08).